General adiposity and adipose tissue distribution in young women from Warsaw (Journal of Medical Science, 2014)
Aim. The aim of this study was to determine the overall adiposity and adipose tissue distribution in young women from Warsaw. Material and methods. The study covered 550 women from Warsaw. The following research methods were applied: bioelectric impedance, measurement of body weight, body height, waist and hip circumference, body mass index (BMI), adipose tissue distribution Waist-to-Hip Ratio (WHR), Waist-to-Height Ratio (WHtR); waist circumference was also analyzed based on the criterion of the International Diabetes Federation (IDF). Results. The average value of body mass index pointed to the correct values within 18.5–24.9 kg/m2 range, while the BMI distribution in the studied group covered a wide range, starting from values characteristic for the state of emaciation up to values indicating IIIo obesity. Analysis of adipose tissue distribution based on WHR indicator showed existence of central adiposity, or abdominal adiposity, in case of more than 60% of the surveyed women. However, based on WHtR indicator that takes into account waist circumference and body height, abdominal obesity was found in case of slightly more than 30% of women. Analysis of the waist circumference measurement showed that abdominal (visceral) adiposity was found in case of half of the surveyed women. Average overall adiposity was 18.5 kg. Adiposity on the left and right sides of the individual body segments did not differ significantly. Conclusion. Overweight and obesity connected to the risk of developing cardiovascular disease exist among young women from Warsaw. Among the surveyed women a significant percentage of people with abdominal (central) type of adiposity was found, which creates the increased risk of cardiovascular disease. Prevention of cardiovascular disease should be based not only on the assessment of the overall adipose tissue and BMI but also on the assessment of its distribution in the body. Young women from Warsaw should be covered by preventive actions in order to prevent the development of cardiovascular disease through health education programs.